The lipid profile of three Malassezia species assessed by Raman spectroscopy and discriminant analysis. (August 2019) - Petrokilidou, Chrysoula; Pavlou, Eleftherios; Gaitanis, Georgios; Bassukas, Ioannis D.; Saridomichelakis, Manolis N.; Velegraki, Aristea; Kourkoumelis, Nikolaos
Abstract: Malassezia yeasts constitute the major eukaryotic cutaneous flora of homoeothermic vertebrates. These lipophilic yeasts are able to cause, trigger, or aggravate common skin diseases under favorable conditions. Species identification and subspecies differentiation is currently based on morphological characteristics, lipid assimilation profile, and molecular tests. Mass spectrometry has been also reported as a reliable, yet costly and labor-intensive, method to classify Malassezia yeasts. Here, we introduce Raman spectroscopy as a new molecular technique able to differentiate three phylogenetically close Malassezia species ( M.globosa, M.pachydermatis, and M.sympodialis ) by examining their lipid metabolic profile. Using Raman spectroscopy, lipid fingerprints of Malassezia cultures on Leeming-Notman agar, were analyzed by spectral bands assignment and partial least squares discriminant analysis. Our results demonstrate differential utilization of lipid supplements among these three species and the ability of Raman spectroscopy to rapidly and accurately discriminate them by predictive modelling. Highlights: Raman spectroscopy is a sensitive and specific approach to adequately differentiate Malassezia cultures at species. The varied uptake and metabolic conversion of fatty acids by Malassezia spp was probed by Raman spectroscopy. Raman spectroscopy and partial least squares-discriminant analysis can classify Malassezia yeasts in culture media.